2015
DOI: 10.1186/s13010-015-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

‘Trust my doctor, trust my pancreas’: trust as an emergent quality of social practice

Abstract: BackgroundGrowing attention is being paid to the importance of trust, and its corollaries such as mistrust and distrust, in health service and the central place they have in assessments of quality of care. Although initially focussing on doctor-patient relationships, more recent literature has broadened its remit to include trust held in more abstract entities, such as organisations and institutions. There has consequently been growing interest to develop rigorous and universal measures of trust.MethodsDrawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…To gain a deeper knowledge about trust in this context, we took a qualitative approach to determine the underlying reasons behind why a person decides to trust a care provider for a certain task. Because very little is known about this context, as previously discussed, and there is no established standard measurement for trust [14], qualitative data collection is the most informative for our purposes.…”
Section: Methodsmentioning
confidence: 99%
“…To gain a deeper knowledge about trust in this context, we took a qualitative approach to determine the underlying reasons behind why a person decides to trust a care provider for a certain task. Because very little is known about this context, as previously discussed, and there is no established standard measurement for trust [14], qualitative data collection is the most informative for our purposes.…”
Section: Methodsmentioning
confidence: 99%
“…(mother) Accordingly, it has been demonstrated that, in diabetes care, trust is related to the need to establish a feeling of stability across different kinds of relationships so as to counter feelings of vulnerability or uncertainty (Cohn, 2015). However, for pre-teens, trust had a different connotation.…”
Section: Trusting Othersmentioning
confidence: 99%
“…Furthermore, the researcher acted as a sounding board, a source of knowledge and inspiration, and an important external driver for participants to persist with reconfigured practices even when this required additional learning and effort in the transitional phase. This generated important social interaction and built relations of trust (Cohn, 2015). Such benefits should not be underestimated, but therein lies a considerable challenge for those driving sustainable eating paradigms.…”
Section: Experimental Homelabs: Outcomes Connections and Contextmentioning
confidence: 99%